"A few bad apples" or "rotten to the core": Perceptions of corporate culture drive brand engagement after corporate scandal. Issue 1 (17th August 2017) - Guckian, Meaghan L.; Chapman, Daniel A.; Lickel, Brian; Markowitz, Ezra M.
Abstract: Following unethical corporate behavior, consumers face decisions on how to engage with brands in the future. Consumers' beliefs about the underlying causes of a corporate scandal may influence future patronage intentions, for example, by influencing perceived likelihood of future wrongdoing. We investigated how beliefs about corporate culture and consumer proximity to the recent Volkswagen diesel emissions scandal influence expectations of future ethical action by Volkswagen Group (VW), feelings of anger, and future brand engagement. Results indicate that beliefs about corporate culture and proximity each independently influence future brand engagement. Specifically, owners who believed "a few bad apples" (rather than a "rotten" corporate culture) caused the scandal reported higher expectations of future ethical action by VW, less anger, and more positive intentions to engage with VW in the future. Those more proximately affected by the scandal, that is, turbocharged direct injection owners, were more likely to be angry and less likely to engage with VW. Expectation of future ethical action and anger mediated the effects of corporate culture on engagement, whereas only anger mediated the effects of proximity. This small set of factors accounted for over half of the observed variance in future brand engagement intentions, highlighting the importance of understanding consumer responses to corporate scandal.